Isomorphism in higher education institutions: an examination of the mission statements of universities in turkey - ATAMAN BERK, GÖKSEL (My University, 2022)
This study aims to examine the mission statements describing the central purposes of universities in order to investigate the similarities in higher education institutions based on the new institutional theory. The new institutional theory suggests that organizations are similar to each other through coercive, mimetic, and normative isomorphism mechanisms. However, the literature states that there is a need for more studies investigating isomorphism in higher education. For this purpose, the current study examines the mission statements of 21 state and foundation universities from seven different regions of Turkey. A thematic analysis was utilized to assess the universities' mission statements using the MAXQDA program. Consistent with the theoretical structure, the research findings show there are similar themes in the universities' mission statements. Furthermore, we found that universities emphasize six common themes in their mission statements: social purposes, research purposes, training purposes, educational purposes, technological purposes, and institutional philosophy. This research makes a theoretical contribution to applying the new institutional theory in higher education research and provides recommendations for future research.
Keywords: New Institutional Theory; Isomorphism; University; Mission Statements; Thematic Analysis; Turkey.